Ligneous periodontitis exacerbated by Behçet's disease in a patient with plasminogen deficiency and a stop-gained variant PLG c.1468C > T: a case report - Yuki Shinoda-Ito; Anna Hirai; Kazuhiro Omori; Hidetaka Ideguchi; Hideki Yamamoto; Fumino Kato; Kyoichi Obata; Tatsuo Ogawa; Keisuke Nakano; Takato Nakadoi; Eri Katsuyama; Soichiro Ibaragi; et al. (BMC, 2023)
Abstract Background Plasminogen serves as the precursor to plasmin, an essential element in the fibrinolytic process, and is synthesized primarily in the liver. Plasminogen activation occurs through the action of plasminogen activator, converting it into plasmin. This conversion greatly enhances the fibrinolytic system within tissues and blood vessels, facilitating the dissolution of fibrin clots. Consequently, congenital deficiency of plasminogen results in impaired fibrin degradation. Patients with plasminogen deficiency typically exhibit fibrin deposits in various mucosal sites throughout the body, including the oral cavity, eyes, vagina, and digestive organs. Behcet's disease is a chronic recurrent systemic inflammatory disease with four main symptoms: aphthous ulcers of the oral mucosa, vulvar ulcers, skin symptoms, and eye symptoms, and has been reported worldwide. This disease is highly prevalent around the Silk Road from the Mediterranean to East Asia. We report a case of periodontitis in a patient with these two rare diseases that worsened quickly, leading to alveolar bone destruction. Genetic testing revealed a novel variant characterized by a stop-gain mutation, which may be a previously unidentified etiologic gene associated with decreased plasminogen activity. Case presentation This case report depicts a patient diagnosed with ligneous gingivitis during childhood, originating from plasminogen deficiency and progressing to periodontitis. Genetic testing revealed a suspected association with the PLG c.1468C > T (p.Arg490*) stop-gain mutation. The patient's periodontal condition remained stable with brief intervals of supportive periodontal therapy. However, the emergence of Behçet's disease induced acute systemic inflammation, necessitating hospitalization and treatment with steroids. During hospitalization, the dental approach focused on maintaining oral hygiene and alleviating contact-related pain. The patient's overall health improved with inpatient care and the periodontal tissues deteriorated. Conclusions Collaborative efforts between medical and dental professionals are paramount in comprehensively evaluating and treating patients with intricate complications from rare diseases. Furthermore, the PLG c.1468C > T (p.Arg490*) stop-gain mutation could contribute to the association between plasminogen deficiency and related conditions.